Effects of the timing of carbohydrate intake on metabolism and performance in soccer players - Noh, K. -W.; Oh, J. -H.; Park, S. (Nutrients, 2023)
This study aims to provide information to improve the performance of athletes comparing the effects of carbohydrate-electrolyte intake before and during exercise on metabolism and performance in soccer players. The study had a single-blind cross-over design. Drust`s protocol is a soccer-specific intermittent exercise test. The carbohydrate-electrolyte intake experiments were divided into three timings: first, pre-exercise; second, half-time; and third, mixed. Eight participants were included in the data analysis (age: 21.32 ± 1.19 years; BMI: 22.69 ± 1.91 kg/m2; height: 176.5 ± 7.52 cm; weight: 69.5 ± 9.18 kg; Vmax: 16.75 0.71 km/h). The results of the mixed test showed a significantly lower respiratory exchange ratio than those of the placebo and half-time tests (p < 0.05). The mixed test showed significantly more fat oxidation than the half-time test (p < 0.05). The running times are placebo (422.13 ± 133.44 s) and mixed (677.38 ± 217.75 s), and the distances are placebo (1577.25 ± 517.02 m) and mixed (2530.00 ± 832.71 m) (p < 0.05). The mixed test showed a significantly lower rating of perceived exertion than the placebo test (p < 0.05). Carbohydrate oxidation and heart rate showed no significant differences between the experiments (p > 0.05). The exercise protocol in this study showed the metabolic response of soccer players to intermittent high-intensity exercise and subsequent endurance exercise. In conclusion, it can be seen that the intake of carbohydrate-electrolytes improves the performance of soccer players, and the effect varies depending on the timing of carbohydrate-electrolyte intake.